PSD3, regulated by PKM2, endows growth and metastasis advantages in esophageal squamous cell carcinoma by modulating EMT progression - Qiqi Zhang; Qing Liu; Shutao Zheng; Tao Liu; Lifei Yang; Yiyi Tan; Xiaomei Lu (Scientific Reports)
Abstract PH and Sect. 7 domain-containing protein 3 (PSD3) has been reported to be associated with some cancers, but its role in esophageal squamous cell carcinoma (ESCC) has not been thoroughly examined. The purpose of this study was to investigate the expression of PSD3 in ESCC and determine whether PSD3 is regulated by pyruvate kinase type M2 (PKM2) to affect the malignant phenotype of ESCC cells. First, we found that PSD3 was highly expressed in ESCC tissues and correlated with ESCC lymph node metastasis. In vitro, PSD3 promoted the proliferation, migration and invasion of ESCC cells. In vivo, PSD3 accelerated ESCC growth and metastasis. Next, the interaction between PSD3 and PKM2 was examined, and the results showed that PSD3 was directly regulated by PKM2. Functionally, PSD3 was regulated by PKM2 to promote the proliferation, migration and invasion of ESCC cells. Mechanistically, PSD3 was regulated by PKM2 to upregulate the expression of Vimentin and Snail and downregulate the expression of E-cadherin. Collectively, all the data we show here demonstrate that PSD3, regulated by PKM2, endows growth and metastasis advantages in ESCC by modulating epithelial-mesenchymal transition (EMT) progression.